Pemodelan Reservoir dan Uji Tekanan Transien Untuk Penentuan Permeabilitas Pada Reservoir Multilayer - Nugraha Mahaputra Perdana, Teja
This study presents the determination of permeability values for each layer of a multilayer reservoir system with a pressure buildup test. This test can be use to determine the value of permeability (k), thickness (h), skin factor (S), and initial reservoir pressure (Pi). Analysis of the pressure buildup test in an analytical solution generally cannot provide the accurate results, especially in a multilayer reservoir that has a distinctive characteristic difference in each layer. Therefore, a numerical simulation was done in this study by using synthetic model to evaluate calculations obtained from analytical solutions. Numerical synthetic models was made by using conventional reservoir simulators with known rock and reservoir fluid data that describe multilayer reservoir systems. A model with radial shape is constructed which consists of four commingled layers so the interlayer only interracts in the wellbore. A single production wells, was placed in the center of the model area. Modify the porosity and permeability number in the area around the production well to provide a wellbore storage effect and skin factor. The production scenarios is done by one production period and one shut-in period. Pressure vs time data, which is the output from the simulation is used as input data in the pressure buildup test analysis with analytic solutions. From analytical calculations, it is evident that this solution cannot directly determine the permeability value of each layer accurately. The values of permeability are not match yet and may exchange between layers. Repeated regression is needed which includes the value of wellbore storage and skin factors in order to obtain permeability values with small errors. In this study, the errors obtained for permeability values could be below 1%. Analysis also include the skin factor, wellbore storage, and initial reservoir pressure. The results are intended to establish the stages of analysis in determining the permeability value of each layer from multilayer reservoir by include the influence effect of wellbore storage and skin factors from numerical simulations using synthetic models.